YTTERBIUM PORPHYRINS COMPLEXES AND THEIR APPLICATION IN MEDICINE - V. D. Rumyantseva; A. E. Shchelkunova; A. S. Gorshkova; Yu. V. Alekseev; I. P. Shilov; A. V. Ivano; E. V. Davydov; A. F. Mironov (Тонкие химические технологии)
Malignant tumors are the second most frequent cause of death after cardiovascular diseases. The photodynamic therapy based on the interaction of laser light with different photosensitizers was discovered in the 20th century as one of treatment methods. When using photosensitizers, the process of singlet oxygen and other active forms generation is observed in both malignant and healthy body tissues, which leads to a number of adverse reactions. More promising diagnostic compounds that do not have these disadvantages are ytterbium porphyrin complexes. These compounds slightly generate singlet oxygen under light irradiation, while maintaining a high level of tumorotropic agents as for therapeutic photosensitizers. This work continues a series of studies devoted to the analysis of physicochemical properties of Yb-complex 2,4-dimetoxyhematoporphyrin IX as a promising marker for fluorescent diagnostics of various tumors. Pharmaceutical compositions based on Yb3+-dimetoxyhematoporphyrin IX dipotassium salt were created. These compositions are capable of accumulating in the sites of inflammation and proliferation in diseases of mucosal membranes and cancer lesions. Toxicological and pharmacokinetic studies were carried out with the use of laboratory animals and volunteers. The analysis results showed that the pharmaceutical compositions are perspective for use in clinical practice.